Risk factors for adverse drug reactions in older inpatients of geriatric wards at admission: Multicenter study. Issue 2 (12th December 2019) - Kojima, Taro; Matsui, Toshifumi; Suzuki, Yusuke; Takeya, Yasushi; Tomita, Naoki; Kozaki, Koichi; Kuzuya, Masafumi; Rakugi, Hiromi; Arai, Hiroyuki; Akishita, Masahiro
Abstract : Aim: To investigate the characteristics of adverse drug reactions (ADR) and their risk factors among very old patients in five geriatric wards in Japan. Methods: A retrospective observational multicenter study was carried out to investigate factors related to ADR in older inpatients from geriatric wards of five university hospitals in Japan. Data including drugs profile and short‐form comprehensive geriatric assessment were obtained from medical charts. ADR were identified from geriatrician's reports. For each ADR, symptoms and causal drugs were clarified, and factors associated with ADR were analyzed statistically. Results: In 1155 patients (52.5% women, mean age 82.8 ± 7.0 years), the proportion with ADR was 15.4%. There was a great variety of signs and symptoms of ADR, and a great variety of drugs suspected to be the cause of ADR. On multiple logistic regression analysis, ADR was significantly associated with an increase in drugs (odds ratio 1.11, 95% CI 1.07–1.16) and emergency admission (odds ratio 2.76, 95% CI 1.82–4.15). Receiver operating characteristic curve analysis showed that the optimal cut‐off number of drugs for predicting ADR was ≥7. Conclusions: In geriatric inpatients, polypharmacy (especially ≥7 drugs) and emergency admission were associated with ADR. Because there was a great variety of ADR in the study, clinicians must consider reviewing all drugs to prevent adverse drugs reactions during admission in this vulnerable population. Geriatr Gerontol Int 2019; : – . Geriatr Gerontol Int 2020; 20: 144–149 .